KARAKTERISTIK PASIEN PENDERITA OTOMIKOSIS DI RUMAH SAKIT ISLAM SITI RAHMAH PADANG TAHUN 2023-2025 - Seres Triola; Nopeliantesa Lovprima; Riki Nova; Haves Ashan (Yayasan Nusantara Hasana Berdikari, 2026)
Otomycosis was a fungal infection of the external auditory canal that commonly occurred in tropical and humid climates, including Indonesia. In addition to humidity, the incidence of otomycosis was influenced by ear-cleaning habits and repeated exposure to water. Therefore, epidemiological data on otomycosis were needed as a basis for effective prevention and management efforts. This study aimed to determine the characteristics of patients with otomycosis at Siti Rahmah Islamic Hospital Padang during the period 2023–2025. This study employed a descriptive quantitative research design. Data collection was conducted using a cross-sectional approach. The sampling technique used was total sampling, with a total sample size of 94 respondents. The data were secondary data obtained from the medical records of patients with otomycosis. The research variables included age, sex, occupation, clinical symptoms, treatment patterns, and complications. The characteristics of patients with otomycosis at Siti Rahmah Islamic Hospital Padang during 2023-2025 were predominantly adults aged 18-59 years (78.7%), female (56.4%), and mostly working indoors (74.5%). The majority of patients presented with clinical symptoms (89.4%). Treatment patterns showed that topical antifungal therapy was the most commonly administered treatment (38.3%). Most patients with otomycosis did not experience complications (71.3%). Patients with otomycosis at RSI Siti Rahmah Padang in 2023-2025 were predominantly adults and female. The main presenting complaint was ear pruritus, and topical antibiotics were the most commonly prescribed therapy. Most patients did not experience complications